Antiprostatic Activities of Hippocratea africana Root Extract and Fractions Against Testosterone-Induced Benign Prostatic Hyperplasia in Rats - Okokon, Jude Efiom; Ekeleme, Daniel; Essien, Grace Emmanuel (Sciences of Pharmacy, 2026)
Hippocratea africana (Willd.) Loes. ex Engl. (Celastraceae) syn. Loeseneriella africana (Willd.) N.Hallé root which is used as medicine traditionally to treat various diseases by the Ibibios was investigated for antiprostatic effect against testosterone-induced benign prostatic hyperplasia (BPH). The dried root powder was cold extracted in 50% ethanol and the extract dissolved in distilled water and partitioned with dichloromethane (DCM) to obtain DCM and aqueous fractions of H. africana root. BPH was induced in groups of male rats (n=5) using testosterone propionate (3 mg/kg). Based on previously determined median lethal dose, the root extract and fractions of H. africana (200-600 mg/kg) were investigated for effects on prostate weight and histology, prostate sensitive antigen (PSA), testosterone levels, lipid profile, oxidative stress markers, semen analysis and testis histology of rats with testosterone propionate–induced BPH. Finasteride (5 mg/kg) was used as standard drug. The root extract/fractions were found to cause significant (p<0.05- 0.01) decreases in PSA and testosterone levels, reductions in prostate and testis weights, improvement of semen volume and health, elevations of antioxidant enzymes (SOD, CAT,GPX) and molecule (GSH) and also reduced MDA level. These results suggest that the root extract and fractions of H. africana possess antiprostatic potentials against testosterone-induced BPH in rats which may be due to the antioxidant activities of its phytochemical constituents.